Addressing the criticisms and critiques of positive psychology: recommendations for improving the science and practice of the field - Jaclyn Gaffaney; Stewart Ian Donaldson (Frontiers in Psychology)
This article presents two checklists designed to help researchers, practitioners, and evaluators address common critiques of Positive Psychology (PP) identified in a recent systematic review. These critiques focus on PP's theorizing, methodology, and its perception as a decontextualized, capitalistic endeavor. The checklists offer practical recommendations for improving future research and practice, with one tailored for researchers and the other for practitioners and evaluators. Key focus areas include self-reflection, cultural sensitivity, methodological diversity, collaboration, and ethical considerations. By acknowledging past critiques and offering concrete solutions, this paper aims to foster a more inclusive and rigorous future for PP.